1997
DOI: 10.1021/jf960794u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Gelation of β-Lactoglobulin AB Purified from Cheddar Whey. 1. Effect of pH on Association As Observed by Dynamic Light Scattering

Abstract: Thermal association of β-lactoglobulin AB (β-Lg) purified from Cheddar whey, a major source of commercial whey ingredients, was studied by dynamic light scattering (DLS). The objective was to observe the effect of the process and/or possible micromolecules in this β-Lg source of commercial relevance. Protein solution (8%, w/v) was heated (25−90 °C) at pH 3.5, 7, and 9.0. DLS data were analyzed according to the method of Cumulants for apparent mean diameter and by the Contin method for percentile size distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…In that study and in the present one, exhaustive purification was not carried out to remove trace peptides so as to examine ␤-Lg in its impurity induced conformational state in which it conceivably exists and functions in food systems. Our data (Haque & Sharma, 1997) indicated a greater degree of association at all stages of heating compared to yet another study using chromatographically pure ␤-Lg (Sharma et al, 1996). The starting mean aggregate diameter (MAD) prior to heating (25˚C) was a reflection of the pore size of the membrane (200 nm) used to remove traces of dust from the sample (Haque & Sharma, 1997).…”
mentioning
confidence: 51%
See 4 more Smart Citations
“…In that study and in the present one, exhaustive purification was not carried out to remove trace peptides so as to examine ␤-Lg in its impurity induced conformational state in which it conceivably exists and functions in food systems. Our data (Haque & Sharma, 1997) indicated a greater degree of association at all stages of heating compared to yet another study using chromatographically pure ␤-Lg (Sharma et al, 1996). The starting mean aggregate diameter (MAD) prior to heating (25˚C) was a reflection of the pore size of the membrane (200 nm) used to remove traces of dust from the sample (Haque & Sharma, 1997).…”
mentioning
confidence: 51%
“…Furthermore, percentile distribution of various micron (>1000 nm) and submicron-sized (<1000 nm) aggregates differed at the different pH conditions studied, conceivably reflecting conformational alteration that facilitate or limit spatial freedom for intermolecular association. This previous study in this series showed that the smallest level of association, the monomeric/dimeric form (1-9 nm range) was only seen at temperatures below 65˚C at pH 3.5, the ubiquitous aggregate size range was 100-599 nm (Agg3), and greatest changes in aggregate size and distribution were detected around 70˚C (Haque & Sharma, 1997). Large, micron-sized aggregates were formed at this temperature and above, concomitant with disappearance of Agg3.…”
mentioning
confidence: 60%
See 3 more Smart Citations